2007
DOI: 10.1140/epjb/e2007-00229-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolving pseudofractal networks

Abstract: Abstract. We present a family of scale-free network model consisting of cliques, which is established by a simple recursive algorithm. We investigate the networks both analytically and numerically. The obtained analytical solutions show that the networks follow a power-law degree distribution, with degree exponent continuously tuned between 2 and 3. The exact expression of clustering coefficient is also provided for the networks. Furthermore, the investigation of the average path length reveals that the networ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 52 publications
(107 reference statements)
4
41
0
Order By: Relevance
“…For example, it has been suggested that for stochastic scale-free networks with degree distribution exponent γ < 3 and network order N, their average distance d(N) behaves as a double logarithmic scaling with N: d(N) ∼ ln ln N [7,6], which is in sharp contrast to the logarithmic scaling obtained for the BRV model addressed here, in despite of the fact that the latter has a degree distribution exponent γ = 1 + ln 3 ln 2 less than 3. Actually, this logarithmic scaling of average distance with network order has also been shown in other deterministic scale-free networks with γ < 3 [19,25,28,36,41,42]. Thus, deterministic scale-free networks present an obvious difference from their stochastic scale-free counterparts in the aspect of structural property of average distance.…”
Section: Analytical Resulstssupporting
confidence: 62%
“…For example, it has been suggested that for stochastic scale-free networks with degree distribution exponent γ < 3 and network order N, their average distance d(N) behaves as a double logarithmic scaling with N: d(N) ∼ ln ln N [7,6], which is in sharp contrast to the logarithmic scaling obtained for the BRV model addressed here, in despite of the fact that the latter has a degree distribution exponent γ = 1 + ln 3 ln 2 less than 3. Actually, this logarithmic scaling of average distance with network order has also been shown in other deterministic scale-free networks with γ < 3 [19,25,28,36,41,42]. Thus, deterministic scale-free networks present an obvious difference from their stochastic scale-free counterparts in the aspect of structural property of average distance.…”
Section: Analytical Resulstssupporting
confidence: 62%
“…It is also interesting to stress that this linear scaling is in contrast to the sub-linear scaling of mean trapping time obtained for the two-dimensional Apollonian network [60] and the pseudofractal scale-free web [67], in spite of the fact that they have a similar topological structure [57,58,59,62,63,64] as that of the Koch network. The reason for this disparity is worth studying in the future.…”
Section: B Analytical Solution For Mean Trapping Timementioning
confidence: 74%
“…Equation (39) also reveals that δ ij is a constant 1. Notice that the linear scaling of the average traverse time with network order has been previously obtained by numerical simulations for the Apollonian networks [37] and the pseudofractal scale-free web [41], both of which have been well studied [52,57,58,59,60,61,62,63,64,65,66,67].…”
Section: First-passage Time For All Nodesmentioning
confidence: 74%
“…First passage time (FPT), which is the time it takes a random walker to reach a given site for the first time, and first return time (FRT), which is the time it takes a random walker to return to the starting site for the first time, are two important quantities inTherefore, the PSFW has attracted lots of attentions in the past several years and much effort has been devoted to the study of its properties, such as degree distribution, degree correlation, clustering coefficient [47,50], diameter [50], average path length [49], the number of spanning trees [51], and eigenvalues [52]. As for random walks on the PSFW, the MFRT for any node v is 2m/d v ; Zhang and etc [53] obtained the recursive relation of the MFPT from any starting node to the hub (i.e., node with highest degree) and then gained the mean trap time to the hub by averaging the MFPTs over all the possible starting nodes.…”
Section: Introductionmentioning
confidence: 99%